Politics of human network in African conflicts : Kamajor/the CDF in Sierra Leone - Okano, Hideyuki (Langaa RPCIG, 2019)
Sierra Leone experienced 11 years' civil war after the incursion of the Revolutionary United Front (RUF) from adjacent Liberia. The war of Sierra Leone is one of the most researched in Africa. However, the foci of studies are mostly on the RUF. Other armed groups are not sufficiently studied. This book focuses on the governmental side of the Kamajor and the Civil Defence Force (CDF). Kamajors were community-based vigilantes mobilised by paramount chiefs in various Mende communities. During the course of the war, the government organised Kamajors into a pro-governmental militia, the CDF. This book examines how human networks worked in the course of the formation of Kamajor and of the CDF. Even though the roles of human networks have been discussed in the realm of African politics, they have been left hypothetical. Few studies demonstrate the whole picture on how neopatrimonialism, patronu-client relations or informal networks function within an organisation. This book describes the course of Kamajor/CDF along with functions of the human networks. In the networks, the threads of human relations are interwoven by subsuming the local, the international and the global dimensions of the armed conflict. Some connect to governmental figures. Others have transnational networks in adjacent Liberia. In the changing situations of the war, some of the relations are maintained, while some relations are disintegrated. Those who emerge as prominent figures in the Kamajor/CDF use their own human networks to obtain resources for the Kamajor/CDF, which in turn, afford themselves higher positions in the force.